Jacobi elliptic function approach to a conformable fractional nonlinear Schrödinger–Hirota equation - Ahmad Sharif (Partial Differential Equations in Applied Mathematics, 2023)
In this present paper we propound the following equation iDtαu+a2Dx2αu+ia3Dx3αu+a4Dx4α+ibDxα|u|2u+iσ|u|2Dxαu+iλDxα|u|2=c1|u|2u+c2|u|4,which is called the generalized nonlinear fractional Schrödinger–Hirota equation with conformable derivative. Actually the principal idea in this study is to use modified Jacobi elliptic function approach to find analytical solutions to the generalized nonlinear fractional Schrödinger–Hirota equation. Moreover, a graphical analysis of the fluctuations of the answers is considered using Mathematica software, which helps to better understand the solutions.